Optimal Switching Sequence Mpc for Four-Leg Two-Level Grid-Connected Converters - Travieso-Torres, J; Travieso-Torres, J (Institute of Electrical and Electronics Engineers Inc., 2024)
This article presents a versatile and effective model predictive current control strategy based on optimal switching sequences for four-leg two-level (4L-2L) grid-connected converters. The proposed control methodology presents an excellent dynamic performance, good tracking of high-frequency reference signals, fixed switching frequency, and well-formed harmonic spectrum, enabling the proposed controller to govern shunt active filters (SAFs) and distributed generation applications based on four-leg converters. Experimental results demonstrate the effectiveness and high-quality performance obtained with the proposed strategy. © 2013 IEEE.